irThe Effect of WaterSoluble Polymers on Felodipine Aqueous Solubility and Complexing Abilities with Natural and Modified β-Cyclodextrin: Icreased aqueous solubility of felodipine by water soluble polymers - Bhanudas Shankar Kuchekar; Minal Raghunath Narkhede (Iranian Journal of Pharmaceutical Sciences, 2007)
Purpose of this study was to investigate the effect of the presence of the watersoluble polymers viz HPMC, PVPand PEG 6000 on aqueous solubility andcomplexation abilities of felodipine with or without presence of β-cyclodextrin (βCD)and HPβCD by phase solubility studies. The data revealed the initial increase in drugsolubility followed by plateau in the presence of relatively low polymer concentrationi.e. 0.25-0.5 %w/v. Phase solubility diagrams of felodipine in ternary systemshowed similar behaviour to binary system without βCD. Addition of water solublepolymer to βCD solution improved βCD solubilizing efficiency due to increase inβCD complexing power toward felodipine. In binary system solubility was found2.5 to about 10 times higher than in water which was further improved in thepresence of 0.25% w/v water soluble polymer. Ternary systems with βCD showedhighest increments in solubility towards felodipine, with 78.8%, 81.8% and 74%improvement after the addition of 0.25% w/v HPMC, PVPand PEG6000,respectively. Our study confirmed that addition of small amounts of hydrophilicpolymer is useful strategy for improving the solublization and complexing abilitiesof cyclodextrins thus allowing less cyclodextrin to be needed to solubilize givenamount of drug. This offers economic advantage. All the polymers under studyshowed synergistic effect on felodipine cyclodextrin solublization by increasingcomplexation efficiency.The highest solubility improvement up to 81.8% wasobtained for βCD ternary system when 0.25% w/v of PVPwas used.